2020
DOI: 10.2196/24087
|View full text |Cite
|
Sign up to set email alerts
|

Use of Telehealth During the COVID-19 Pandemic: Scoping Review

Abstract: Background With over 37.8 million cases and over 1 million deaths worldwide, the COVID-19 pandemic has created a societal and economic upheaval of unparalleled magnitude. A positive transformation has been brought about by innovative solutions in the health care sector that aim to mitigate the impact of COVID-19 on human health. For instance, the use of telehealth has been on the rise amidst this public health emergency. Objective Given the unprecedente… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
375
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 504 publications
(391 citation statements)
references
References 40 publications
7
375
0
9
Order By: Relevance
“…It is noteworthy that a majority of the articles in this review were written in the context of high-income countries, notably the United States of America (USA), and were published predominantly in geriatrics-related journals published in those countries. This is similar to other studies, which have found that the vast majority of published articles on telehealth were from studies carried out in high-income countries, and a vast majority of them were from the USA [ 9 ]. In high-income countries, access to and use of telehealth for older people has improved during the pandemic.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It is noteworthy that a majority of the articles in this review were written in the context of high-income countries, notably the United States of America (USA), and were published predominantly in geriatrics-related journals published in those countries. This is similar to other studies, which have found that the vast majority of published articles on telehealth were from studies carried out in high-income countries, and a vast majority of them were from the USA [ 9 ]. In high-income countries, access to and use of telehealth for older people has improved during the pandemic.…”
Section: Discussionsupporting
confidence: 89%
“…With the onset of the COVID-19 pandemic, a rapid scale up of telehealth services was noted globally as countries began to relax legal restrictions regarding the use of telehealth for the provision of health care services. While insurance companies in some countries had included limited telehealth services in their coverage pre-COVID-19, the scale and scope of coverage for telehealth have rapidly increased during the pandemic [ 8 , 9 ]. There is now a growing optimism on the global use of telehealth services in several specialties, and the field of geriatrics is no exception.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, our research clearly demonstrates that telehealth appointments resulted in positive overall patient satisfaction metrics compared with other studies, which have consistently shown a strong association between telehealth utilization and increased patient satisfaction both pre-and intra-pandemic. 1,5,8,9,12…”
Section: Discussionmentioning
confidence: 99%
“…The most recent data available demonstrate that telehealth utilization has effectively assuaged health care delivery challenges amid the current pandemic. 3,4,9 A comprehensive review of COVID-related telehealth literature was recently conducted by Doraiswamy et al, which spanned the first 6 months of the pandemic. 9 In 84.9% of the 543 articles identified, the authors indicated a positive sentiment about the use of telehealth.…”
mentioning
confidence: 99%
See 1 more Smart Citation